2005
DOI: 10.1088/0951-7715/19/1/012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical complexity of discrete-time regulatory networks

Abstract: Genetic regulatory networks are usually modelled by systems of coupled differential equations, and more particularly by systems of piecewise affine differential equations. Finite state models, better known as logical networks, are also used. In this paper we present a class of models of regulatory networks which may be situated in the middle of the spectrum; they present both discrete and continuous aspects. They consist of a network of units, whose states are quantified by a continuous real variable. The stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…In this way, the dynamics of gene regulations is modeled at various levels [13] and using different mathematical techniques [9]. The simplest approaches include boolean networks [10] and discretetime maps [11], while more detailed analysis requires 1D [14] or 2D [12] continuous-time ODE, that can also involve a time-delayed action [15]. Analytical studies of GRN models involving small networks revealed the complexity of their dynamical patterns [14], with the system of two interacting genes solved in detail [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the dynamics of gene regulations is modeled at various levels [13] and using different mathematical techniques [9]. The simplest approaches include boolean networks [10] and discretetime maps [11], while more detailed analysis requires 1D [14] or 2D [12] continuous-time ODE, that can also involve a time-delayed action [15]. Analytical studies of GRN models involving small networks revealed the complexity of their dynamical patterns [14], with the system of two interacting genes solved in detail [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest approaches include boolean networks [10] and discretetime maps [11], while more detailed analysis requires 1D [14] or 2D [12] continuous-time ODE, that can also involve a time-delayed action [15]. Analytical studies of GRN models involving small networks revealed the complexity of their dynamical patterns [14], with the system of two interacting genes solved in detail [11,12]. General relationship between structure and function of large GRN was examined, with particular emphasis on their collective dynamics [16], information processing [17], flexibility [10], and functional organization [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a special case, genetic regulatory networks (GRNs) consisting of DNA, RNA, proteins, small molecules and their mutual regulatory interactions, have become an important new area of research in the biological and biomedical sciences and received widely attention recently (Becskei and Serrano 2000;Bolouri and Davidson 2002;Weaver et al 1999;De Jong 2002;Smolen et al 2000). Several models have been developed to investigate the behaviors of the GRNs, for example, Boolean models (Weaver et al 1999), the differential equation models (De Jong 2002;Smolen et al 2000), the Petri net models (Chaouiya 2007) and discrete time piecewise affine model (Lima and Ugalde 2006;Coutinho et al 2006). Among them, GRNs in the form of differential equation models have been well studied in He and Cao (2008), Ren and Cao (2008), Ribeiro et al (2006) and Cao and Ren (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to consider stochastic delay effects in GRNs. In addition, as pointed out in Lima and Ugalde (2006), Coutinho et al (2006) and Cao and Ren (2008), some GRN models are discrete-time dynamical systems which can be viewed as an extension of discrete-time delay systems and are more important than their continuous-time counterpart in a sense. These kinds of discrete-time models are directly inspired by the systems of differential equations mentioned above, though they do not correspond to a time discretization of the differential equations but rather to a natural discrete-time version of them.…”
Section: Introductionmentioning
confidence: 99%
“…We will say that the orbit or controlled trajectory {x t } ∞ t=0 is uniformly separated 1 In previous works [2,11] it has been considered less general interaction functions defined as follows. For each interaction (u, v) ∈ A there are associated a sign σuv ∈ {−1, 1}, and a threshold Tuv ∈ (0, 1).…”
mentioning
confidence: 99%